The Increasing of Papua People Intelegency in Papua Through DHA Intake With Natural Ingredients - Audi Satriyanto (Faculty of Public Health, Andalas University, 2016)
In the era of globalization and free markets in 2010-2020, all societies are needed to be able to compete with other nations which had already advanced, including the readiness of Indonesian human resources who excel in order to process natural resources plentiful for the welfare of society. Currently there are no government programs through health centers to improve the quality of human resources through the development of the Maternal and Child Health. The method of the health center program in Papua can be done through two programs such as supplementary feeding program for pregnant women, nursing mothers and early age children, regularly. In addition, family education program by feeding natural foods such as chicken eggs in mountainous areas and deep sea fishing to coastal areas in Papua are also important. DHA-rich food sources such as eggs and fish in the sea is a natural substance that is easily obtained and developed in almost all areas of Papua. Both of these programs are expected to provide a brief understanding intake of DHA is important for brain growth and development of infants and toddlers in the future of the family in preparing excellent generation of the Papuan, especially in rural societies.